Hypophosphatemia as Unusual Cause of ARDS in Cushing’s Syndrome Secondary to Ectopic CRH Production. A Case Report - Stefania Mondello; Vincenzo Fodale; Salvatore Cannav; Carmela Aloisi; Barbara Almoto; Michele Buemi; Letterio B. Santamaria (The Scientific World Journal)
Hypophosphatemia is an unusual cause of acute respiratory distress syndrome (ARDS). We describe a hypophosphatemia-related ARDS case report of a 50-year-old woman with ACTH dependent Cushing's syndrome secondary to ectopic CRH production. The patient clinically showed hypotension tachypnea and increasing dyspnea. Laboratory data showed carbohydrate intolerance, severe hypokalemia, and hypophosphatemia. Arterial blood gases measurement revealed hypocapnia and elevation in bicarbonate values. Chest X-ray showed diffuse bilateral alveolar infiltrates similar to acute pulmonary edema and Kerley's striae. Chest CT scan evidenced diffuse ground glass opacification, bilateral patchy consolidation, and fibrosis, compatible with the recovery phase of ARDS. Clinical symptoms and laboratory examinations supported the diagnosis of ARDS. The patient was managed with supplemental potassium, octreotide, and oxygen therapy. Hypophosphatemia was managed by treating the underlying disorder. Successive surgical removal of the adrenal gland led to complete resolution of Cushing's syndrome. In conclusion, although rare and associated with specific risk factors, hypophosphatemia should be suspected in patients who develop unexplained ARDS.